2016
DOI: 10.1039/c6cp02057g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the bipolar effect in the thermoelectric material CaMg2Bi2 using a first-principles study

Abstract: The bipolar effect in relatively narrow band-gap thermoelectric (TE) compounds is a negative process deteriorating the TE properties particularly at higher temperatures. In this work, we investigate the TE performance of the compound CaMg2Bi2 using the first-principles calculation and semi-classical Boltzmann transport theory in combination with our experimental data. It is revealed that this compound exhibits a remarkable bipolar effect and temperature-dependent carrier concentration. The bipolar effect impos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 47 publications
(87 reference statements)
4
53
1
Order By: Relevance
“…While the calculation of this effect is beyond the present work, we qualitatively analyzed the bipolar impact to S by calculating the contribution of thermally generated charge carriers ( Figures S23 and S24). 64 Results obtained clearly showed that in spite of the lower bandgap of Bi-CASe, and thus the higher charge carrier concentrations associated to thermal generation, the reduced effective mass for electrons in this compound should translate in a lower contribution of the minority carriers to S and thus to an overall higher Seebeck coefficient. A bipolar contribution could also explain the differences in the temperature dependence of κ L between Bi-CASe and pure CASe, but this point is to be confirmed.…”
Section: Resultsmentioning
confidence: 92%
“…While the calculation of this effect is beyond the present work, we qualitatively analyzed the bipolar impact to S by calculating the contribution of thermally generated charge carriers ( Figures S23 and S24). 64 Results obtained clearly showed that in spite of the lower bandgap of Bi-CASe, and thus the higher charge carrier concentrations associated to thermal generation, the reduced effective mass for electrons in this compound should translate in a lower contribution of the minority carriers to S and thus to an overall higher Seebeck coefficient. A bipolar contribution could also explain the differences in the temperature dependence of κ L between Bi-CASe and pure CASe, but this point is to be confirmed.…”
Section: Resultsmentioning
confidence: 92%
“…Figure a is a schematic illustration of the bipolar effect in the thermoelectric materials, in which if a temperature gradient is imposed on a thermoelectric material with the hot‐end and cold‐end, more excitation of electrons/holes near the hot‐end than the cold‐end and more annihilation of electrons/holes near the cold‐end than the hot‐end will take place . This implies that more heat will be absorbed near the hot‐end due to the electron/hole excitation and more heat will be released near the cold‐end due to the electron/hole recombination, which enlarges κ . Also, the bipolar effects degrade S , because the thermally excited minority carriers have opposite S and offset those of majority ones …”
Section: Band Gap Enlargementmentioning
confidence: 99%
“…This implies that more heat will be absorbed near the hot‐end due to the electron/hole excitation and more heat will be released near the cold‐end due to the electron/hole recombination, which enlarges κ . Also, the bipolar effects degrade S , because the thermally excited minority carriers have opposite S and offset those of majority ones …”
Section: Band Gap Enlargementmentioning
confidence: 99%
“…They reduce the Seebeck coefficient as the minority charge carriers contribute significantly. This is generally observed for very narrow bandgap semiconductors (E g < 0.5 eV) [13,14]. What is commonly observed is for an ideal metal, they possess high electrical conductivity and low thermal conductivity.…”
Section: Introductionmentioning
confidence: 78%